2015
DOI: 10.1073/pnas.1501072112
|View full text |Cite
|
Sign up to set email alerts
|

Generating new prions by targeted mutation or segment duplication

Abstract: Yeasts contain various protein-based genetic elements, termed prions, that result from the structural conversion of proteins into self-propagating amyloid forms. Most yeast prion proteins contain glutamine/asparagine (Q/N)-rich prion domains that drive prion activity. Here, we explore two mechanisms by which new prion domains could evolve. First, it has been proposed that mutation and natural selection will tend to result in proteins with aggregation propensities just low enough to function under physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…The Ross group previously demonstrated that the prion-forming activity could be artificially generated with as few as two mutations, suggesting that many non-prion Q/N-rich proteins may be just a small number of mutations from acquiring aggregation or prion activity (Paul et al, 2015). Our data, coupled with phylogenetic analysis of Lsb proteins, clearly demonstrates that such an acquisition has indeed happened in the process of yeast evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The Ross group previously demonstrated that the prion-forming activity could be artificially generated with as few as two mutations, suggesting that many non-prion Q/N-rich proteins may be just a small number of mutations from acquiring aggregation or prion activity (Paul et al, 2015). Our data, coupled with phylogenetic analysis of Lsb proteins, clearly demonstrates that such an acquisition has indeed happened in the process of yeast evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Prion formation assays were performed as previously described (64). Briefly, cells expressing a given hnRNPA2-Sup35 fusion as the sole copy of Sup35 were transformed with either an empty vector (pKT24 [65]) or a plasmid expressing the matching PrLD-GFP fusion under the control of the GAL1 promoter.…”
Section: Methodsmentioning
confidence: 99%
“…Foci formation assays were performed as described previously. 27 Briefly, yeast strains yER632, yER1019, and yER1615 were transformed with TRP1 plasmids expressing each PrLD-GFP from the GAL1 promoter. Strains were grown in galactose/raffinose dropout medium lacking tryptophan for 24 hours, and then imaged by confocal microscopy.…”
Section: Foci Formationmentioning
confidence: 99%
“…23,24 PAPA scans proteins for regions of intrinsic disorder, and scores the prion propensities of these regions. 25 PAPA has proven effective at predicting the prion-like activity of Q/N-rich PrLDs; 14 designing mutations to modulate the aggregation activity of PrLDs; [26][27][28] designing synthetic prion-forming domains; 24 and predicting the effects of some disease-associated mutations in human PrLDs. 29 However, PAPA still has substantial limitations.…”
Section: Introductionmentioning
confidence: 99%